Islamic Political Law in Economic Warfare: Indonesian Economic Policy in the Global Economic Struggle - Yayan Muhammad Royani; Nazar Nurdin (Universitas Wahid Hasyim Semarang, 2024)
The era of globalization has shifted the form of military warfare to hybrid warfare involving economic warfare. The contribution of Islamic political law thinking is needed for Indonesia in addressing these issues. This paper is prepared using a qualitative-descriptive method. Data collection is done using desk research and annotated bibliography methods. Three approaches are utilized: textual-contextual, Islamic legal sociology, and comparative. The research results explain that Islamic Political Law is an instrument of political policy for Islamic countries in governance, including in both wartime and peacetime situations. For the Indonesian context, Islamic political law adapts to the development of the nation-state, where Indonesia is considered a state based on agreements or peace, positioning it similarly to Islamic countries. Therefore, Islamic political law thinking is currently needed in building civilization in the era of globalization, especially in dealing with new-style colonization or neo-colonialism. Islamic political law can contribute to the formulation of Indonesian economic policies in facing global economic warfare. The concept of